Twentieth-century British and Irish poetry Hardy to Mahon - O'Neill, Michael 1953-; Callaghan, Madeleine (Blackwell guides to criticism, 2011)
"Featuring contributions from some of the major critics of contemporary poetry, Twentieth-Century British and Irish Poetry offers an accessible, imaginative, and highly stimulating body of critical work on the evolution of British and Irish poetry in the twentieth-century. Covers all the poets most commonly studied at university level courses. Features criticisms of British and Irish poetry as seen from a wide variety of perspectives, movements, and historical contexts. Explores current debates about contemporary poetry, relating them to the volume's larger themes. Edited by a widely respected poetry critic and award-winning poet."--Provided by publisher.